2001
DOI: 10.1053/jvet.2001.20325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Canine Total‐Elbow Arthroplasty System: A Preliminary Study in Normal Dogs

Abstract: Based on 1-year data, TEA can be successfully performed in dogs and could be considered as a treatment alternative for adult dogs with severe osteoarthritis and lameness of the elbow joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 14 publications
(19 reference statements)
4
39
0
Order By: Relevance
“…The TEA system that we evaluated was a nonconstrained system using 2 components, a humeral and radioulnar component, which required cement fixation. The design of the components was modified from those previously reported 8 . The principal changes in the humeral component were angulation of the stem, altered lateral grooves for increased surface area, and rounding of the articulating surface (Fig 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TEA system that we evaluated was a nonconstrained system using 2 components, a humeral and radioulnar component, which required cement fixation. The design of the components was modified from those previously reported 8 . The principal changes in the humeral component were angulation of the stem, altered lateral grooves for increased surface area, and rounding of the articulating surface (Fig 1).…”
Section: Methodsmentioning
confidence: 99%
“…Computer‐assisted force platform gait analysis was performed using a biomechanical platform (OR6‐6‐1000; Advanced Mechanical Technology, Inc., Watertown, MA) embedded in an 8‐m walkway. Velocity and acceleration were measured as previously described 8 . Dogs were walked across the platform (trial velocity between 1.10 to 1.40 m/s, acceleration variation ± 0.5 m/s 2 ), and ground‐reaction forces for the forelimb and hindlimb were recorded (Sharon Software, Inc, Dewitt, MI) for the first 5 valid trials obtained for each limb.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge, this is the first study to objectively evaluate a canine elbow arthroplasty system's efficacy to replicate the axis of the joint. Previous reports (Conzemius et al , ) have not evaluated this parameter. An arthroplasty system employing components that are cemented separately rather than placed as a single unit may have the potential for greater postoperative variation from the preoperative COR axis.…”
Section: Discussionmentioning
confidence: 95%
“…Canine elbow arthroplasty was first described by Lewis (), who developed a constrained system implanted into research dogs, the results of which were never published, but which was associated with a high clinical complication rate and the project was subsequently abandoned. Conzemius & Aper () described a semi‐constrained cemented elbow arthroplasty which was implanted in healthy research dogs (Conzemius et al ) and subsequently 20 dogs with severe elbow osteoarthritis (Conzemius et al ). Objective force‐plate analysis in this latter study revealed “satisfactory” outcomes in 80% of dogs; however, up to 20% of patients have been reported to experience serious complications with this system including infection, luxation and humeral condylar or ulnar fracture (Conzemius et al 2003, Dejardin & Guillou , Innes ).…”
Section: Introductionmentioning
confidence: 99%